The significance of specific IgM antibody in the diagnosis of rubella employing the immunofluorescence technique - Iwakata, S. (1972)
The applicability of the immunofluorescence (IF) test to the diagnosis of primary rubella infection was investigated. The test is based on the detection of rubella-specific antibodies in the IgM fraction of immunoglobulins. The results indicate the usefulness of the IF test for the diagnosis of primary rubella infection on a single serum specimen collected at a proper time. The test is also of value in the differentiation of primary infection from reinfection, since in reinfection no rubella-specific antibodies are found in the IgM fraction. The test is also valuable for the detection of fetal infection in utero since the persistence of IgM antibodies in pregnant women is indicative of fetal infection.